2019
DOI: 10.1039/c9sc03546j
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring polymer dispersity and shape of molecular weight distributions: methods and applications

Abstract: This review explores the different synthetic methods by which dispersity and MWD shape can be tuned and discusses the different properties and applications where this variation is beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
170
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(174 citation statements)
references
References 121 publications
2
170
1
1
Order By: Relevance
“…Technically, two approaches are usually adopted to modulate molecular weight distribution. 20 One is to control the polymerization process. The development of living/ controlled polymerization makes complicated molecular design and "narrow" molecular weight distribution possible.…”
Section: Introductionmentioning
confidence: 99%
“…Technically, two approaches are usually adopted to modulate molecular weight distribution. 20 One is to control the polymerization process. The development of living/ controlled polymerization makes complicated molecular design and "narrow" molecular weight distribution possible.…”
Section: Introductionmentioning
confidence: 99%
“…[10] For self-assembly in solution, Eisenberg had shown that bimodal distributions can influence the shape of nanoaggregates. [11] More examples like this exist in literature (the reader is referred to ref [12] for details), hence showing the validity of the concept and the value of further exploration of the synthetic access to such materials.…”
Section: Doi: 101002/macp202000234mentioning
confidence: 87%
“…[15] Yet, first very promising advances have been made toward controlling the broadness of molecular weight distributions. [12] Figure 1 summarizes the four principle pathways that may be chosen to achieve such aim. Varying dispersities can be accessed from RDRP (and in part from anionic polymerization) via i) direct manipulation of the control equilibrium governing the growth process, ii) via applying a specific initiation profile over the cause of a polymerization, by iii) arbitrary machine-learning methods and last but not least iv) blending of different polymer samples post-polymerization.…”
Section: Doi: 101002/macp202000234mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Furthermore, there have been various reports on the inuence of block length and Đ on polymer microphase behaviour, which has a direct inuence on bulk properties. [14][15][16][17][18][19] While these reports provide important information regarding the inuence of block size and midblock MWD breadth on elastomeric properties, there remains an opportunity to use the entire endblock MWD shape as a means to ne-tune TPE properties.…”
Section: Introductionmentioning
confidence: 99%